Perancangan Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) Berbasis Mobile (Studi Kasus: SMPS Alwasliyah 40 Tinokkah) - Alda, Muhamad; Erlina, Fazira; Nasution, Ratna Sabrina; Laila, Umu (MODELING: Jurnal Program Studi PGMI, 2023)
The New Student Acceptance Process (PPDB) which is being carried out at SMPS Alwasliyah 40 Tinokkah is currently still being carried out manually. Therefore there are many problems that arise such as slow data entry, long and unconducive queues, registration files that are not neatly arranged and even files that are damaged or lost, and prospective students who sometimes have difficulty getting information to carry out the registration process. Along with the rise of increasingly sophisticated technological developments, researchers provide solutions to problems that exist at SMPS Alwasliyah 40 Tinokkah. To be able to overcome the problems that occur, a Mobile-Based New Student Acceptance Information System Design was created. This study uses the SDLC (System Development Life Cycle) Method in building the system. The end result of this information system design is expected to provide convenience to access information and the registration process so that the process of accepting new students is carried out effectively and efficiently.